Daughters of (re)imagined early childhood education : reflective narratives of black women educators in Texas during Covid-19 - Green, Meghan L. (Emerald Publishing Limited, 2025)
Daughters of (Re)Imagined Early Childhood Education: Reflective Narratives of Black Women Educators in Texas during Covid-19 delves into the transformative journeys of seven Black women early childhood educators in north Texas from 2020 to 2022. Amidst the challenges of a global pandemic and the socio-political upheaval brought by anti-critical race theory legislation, these educators reflect on how their intersecting identities shaped their unique pedagogical approaches. This compelling book highlights the personal growth and pedagogical evolution of these educators, emphasizing the need to move beyond superficial niceties and color blindness in early learning spaces. By centering the lived experiences of Black women on the front lines of education during crises of health and racial injustice, this book offers invaluable insights for early childhood educators, teacher educators, and researchers engaged in critical qualitative and participatory action research. Daughters of (Re)Imagined Early Childhood Education invites educational stakeholders to learn from these narratives, challenging them to question the status quo and envision a more equitable future for early childhood education. This collection is a vital addition to the literature, showcasing the resilience and innovation of Black women educators in a time of unprecedented change.
Includes index.
Keywords: Women teachers, Black -- Texas.; COVID-19 Pandemic, 2020-2023 -- Influence.; Education -- Philosophy, Theory & Social Aspects.; Teaching staff.; Philosophy and theory of education.; elektronické knihy; electronic books